Experimental characterizations of hybrid natural fiber-reinforced composite for wind turbine blades - Temesgen Abriham Miliket; Mesfin Belayneh Ageze; Muluken Temesgen Tigabu; Migbar Assefa Zeleke (Heliyon, 2022)
Performances of hybrid Natural Fiber-Reinforced Composites (NFRCs) from E-glass, Nacha (Hibiscus macranthus Hochst. Ex-A. Rich.), and Sisal (Agave sisalana) fibers are investigated for wind turbine blades applications. The process of composite manufacturing was getting started with harvesting and extracting the fibers from undesired constituents. To improve the interfacial interaction between fibers, it was further treated with 5% of NaOH and remnants removal. The experiment was performed based on the Taguchi method, specifically with L16 orthogonal array. Four levels of a natural fiber weight ratio (i.e. 5%, 10%, 15 %, and 20%) were considered during the composite preparations process while the weight of glass fiber was maintained at 5% and 10%. The composites are manufactured using the hand lay-up method, and the test specimens are as per American Society for Testing and Materials (ASTM) standards. Then, tensile, compressive, and flexural tests were carried out using a universal testing machine (UTM). Analysis of variance (ANOVA) was employed to determine the factors which affect the experimental responses. Hence, in the main effect, it was confirmed that Nacha fiber (%wt of N) significantly contributes to tensile, compressive, and flexural strength at a 95% level of confidence. Furthermore, the optimal fiber compositions of composites are determined based on a higher signal-to-noise ratio (S/N) for the corresponding strengths.